In Situ Monitoring of Unique Switching Transitions in the Pressure-Amplifying Flexible Framework Material DUT-49 by High-Pressure 129Xe NMR Spectroscopy - Schaber, Jana; Krause, Simon; Paasch, Silvia; Senkovska, Irena; Bon, Volodymyr; Toebbens, Daniel M.; Wallacher, Dirk; Kaskel, Stefan; Brunner, Eike (Journal of Physical Chemistry C, 2017)
The pronounced flexibility of special metal-organic frameworks (MOFs), so-called soft porous crystals, is attracting increasing research interest. Studies of host-guest interactions in such materials are especially powerful if the measurements are performed in situ. 129Xe NMR spectroscopy is favorable because it provides characteristic, structure-sensitive parameters such as chemical shifts. The combination of high-pressure xenon adsorption with 129Xe NMR spectroscopy was used to elucidate the adsorption-induced phase transitions in the recently discovered pressure-amplifying framework material DUT-49, showing a unique negative gas adsorption (NGA) transition. In the open-pore state, DUT-49op exhibits a hierarchical pore system involving both micro- and mesopores. After reaching a critical relative pressure of ca. 0.15, adsorbed xenon induces mesopore contraction, resulting in a purely microporous contracted-pore phase. This contraction is accompanied by release of xenon from the mesopores. Further increase of the pressure initiates the recovery of the mesopores without any indication of a structural intermediate in the NMR spectra. According to the NMR data, the structural transition induced by xenon is a collective, stepwise phenomenon rather than a continuous process. This is the first time that NGA has been studied by directly monitoring the guest and its interaction with the host framework. (Graph Presented).
CRIS-Team Scopus Importer:2022-04-14